Science@IIUM Issue 2 - Saad, Shahbudin; Mohammad Noor, Normawaty; Razali, Azaima; Zahaba, Maryam; Ahmad, Norfaieqah; Abdul Razak, Rashidah; Che Othman, Siti Fairuz; Abd Halim, Khairul Bariyyah; Abdullah, Nor Azahana; Norizan, Siti Fatimah; Mohd Ikhsan, Amar Muhsin (Kulliyyah of Science, IIUM Kuantan, 2019)
Science@IIUM is a magazine that celebrates the members of Kulliyyah of Science, IIUM. Through interviews, image stories and curated content, Science@IIUM highlights the success and anecdotes from those who explore and challenge themselves in academics and also in other areas.